Contamination profiles of selected PCB congeners, chlorinated pesticides, PCDD/Fs in Antarctic fur seal pups and penguin eggs - SCHIAVONE, A.; CORSOLINI, S.; BORGHESI, N.; FOCARDI, S. (Chemosphere, 2009)
The aim of this study was to investigate levels of some major environmental contaminants, such as polychlorinated biphenyls (PCBs), polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) and organochlorine pesticides in Antarctic samples. Concentrations of some persistent organic pollutants (POPs) were investigated in Antarctic fur seal pups and eggs of three species of penguins. Dichloro-diphenyl-trichloroethane (DDT) was the main pollutant, followed by PCBs; other organochlorine compounds such as hexachlorobenzene (HCB) and PCDD/Fs were usually found only in minor quantities. Adélie penguin eggs had significantly higher mean PCB concentrations (p < 0.05) compared to the other two penguin species, but there was no difference in DDT levels (p > 0.05). TEQ values in fur seal blubber in our study were one order of magnitude lower than those considered to elicit physiological effects in aquatic mammals. In general, POP concentrations in our samples suggested that likely the study populations were not currently at risk for adverse health effects, but indicated a clear need for further monitoring to assess the presence and time trend of a broad range of contaminants, mainly emerging POPs thought to be increasing in polar regions.